Penerapan Strategi Pembelajaran The Power Of Two sebagai Upaya Meningkatkan Aktifitas dan Prestasi Belajar IPS Siswa Kelas VIII SMP Negeri 5 Seteluk - Syamsul Jauhari (Yayasan Pembina Lembaga Pendidikan (YPLP) PGRI Kabupaten Sumbawa Barat - NTB - Indonesia, 2020)
This study aims to determine the effectiveness of the application of the power of two strategy in increasing student activity in social studies learning, and to determine whether the application of this strategy can improve student learning achievement, as well as to determine the response of class VIII students of SMP Negeri 5 Seteluk to social studies learning with strategies. the power of two. This research is a classroom action research conducted in class VIII SMP Negeri 5 Seteluk. Data collection was done by using observation sheets, cycle tests, questionnaires, documentation and interviews. The data on learning achievement and student activities in learning were analyzed using comparative descriptive. The results of data analysis showed that student learning achievement had increased. This can be seen from the data from the cycle test results that have increased. Before the study, completeness of classical learning was only 31.81%, in the first cycle it increased to 59.09%, and in the second cycle it increased again to 86.36%. For student learning activities in the learning process an average of 18.90% increased, while student learning activities in pairs increased by 18.70% on average. Increased learning achievement and student learning activities are also followed by an increase in psychomotor abilities which is shown by an increase in students' ability in percentage